Pengaruh Kreativitas dan Inovasi Terhadap Kewirausahaan UMKM Food Court Pasar Rame Wiyung - Erlambang Budi Darmanto; Anggi Kartika Kurnia Sari (Yos Soedarso Economic Journal (YEJ), 2020)
Â This research was conducted at the Rame Wiyung Market Food Court. The objective of this research is to find out how much influence creativity and innovation have on entrepreneurship of the Rame Wiyung market food court. This research is a quantitative correlational type that uses three variables, namely the variable creativity (X1), innovation (X2), entrepreneurship (Y), and the validity test of the data used is validity test, reliability test, and hypothesis testing using simple regression test, namely the analysis. compare the value of t table and t count and multiple regression test whose analysis compares between F count with F table. The data collection techniques used were questionnaires and interviews.The results of the adjusted R2 regression (Coefficient of Determination) are explained by the independent variable (X), namely creativity (X1) and innovation (X2) of 92.5%, while the remaining 7.5% is explained by other factors that are not hypothesized or other variables not included in the study.Â Keywords: Creativity; Innovation; Entrepreneurship.